Random amplified polymorphic DNA (RaPD) markers readily distinguish crytic mosquito species(diptera:culicidae) - Budi Mulyaningsih, Budi Mulyaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
cr